A Comparison of Cooling Techniques to Treat Cardiac Arrest Patients with Hypothermia. (12th May 2011) - Finley Caulfield, Anna; Rachabattula, Shylaja; Eyngorn, Irina; Hamilton, Scott A.; Kalimuthu, Rajalakshmi; Hsia, Amie W.; Lansberg, Maarten G.; Venkatasubramanian, Chitra; Baumann, J. J.; Buckwalter, Marion S.; Kumar, Monisha A.; Castle, James S.; et al.
Abstract : Introduction . We sought to compare the performance of endovascular cooling to conventional surface cooling after cardiac arrest. Methods . Patients in coma following cardiopulmonary resuscitation were cooled with an endovascular cooling catheter or with ice bags and cold-water-circulating cooling blankets to a target temperature of 32.0–34.0 ∘ C for 24 hours. Performance of cooling techniques was compared by (1) number of hourly recordings in target temperature range, (2) time elapsed from the written order to initiate cooling and target temperature, and (3) adverse events during the first week. Results . Median time in target temperature range was 19 hours (interquartile range (IQR), 16–20) in the endovascular group versus . 10 hours (IQR, 7–15) in the surface group (P = .001 ). Median time to target temperature was 4 (IQR, 2.8–6.2) and 4.5 (IQR, 3–6.5) hours, respectively (P = .67 ). Adverse events were similar. Conclusion . Endovascular cooling maintains target temperatures better than conventional surface cooling.